Влияние физико-химических свойств высокопрочных порошков синтетического алмаза на эксплуатационные характеристики бурового инструмента - Новиков, Н.В.; Богатырева, Г.П.; Ильницкая, Г.Д.; Богданов, Р.К.; Исонкин, А.М.; Закора, А.П.; Невструев, Г.Ф.; Зайцева, И.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The results of studies of physical-chemical properties of high-strength synthetic diamond grinding powders and dependence of operational (working) characteristics of drilling tools from these properties are presented in this report. The results of studies of an effect of thermal treatment on strength and magnetic characteristics of these powders are also presented. It has been ascertained that a use of diamond grinding powders with high uniformity by strength reduces wear of working elements of drilling tools, i. e. wear-resistance of drilling tools increases.